Eutectic dendrite growth in undercooled Fe83B17 alloy: Experiments and modeling. (August 2015) - Kuang, Wangwang; Karrasch, Christian; Wang, Haifeng; Liu, Feng; Herlach, D.M.
Abstract : The Fe83 B17 eutectic alloy was undercooled by an electromagnetic levitator ranging up to an undercooling 217 K and the recalescence fronts were in-situ recorded by a high-speed camera. The measured growth velocity as a function of undercooling was well predicted by the current eutectic dendrite model for concentrated alloys with a non-linear phase-diagram but not the previous models for dilute alloys with a linear phase-diagram.